Contribuição para o estudo de estações arqueohistóricas em Cabo Verde : os concelhos de Salamanza e João d´Évora (Ilha de S. Vicente) - Rodrigues, M. Conceição (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
With this work we present the results of the first phase of the archaeological excavation that took place on the shell middem discovered in 1913 by O. G. S. Crawford, in the Salamanza Bay - St. Vincent Island, Cape Verde. In the second part of this work we present the study of the materiais collected bythis Archaeologist in the shell middems of João d'Évora Bay. The prospecting and collection of the sherds were only carried out in 1998 and it followed a visit to the shell middem four years ago. The archaeological excavation was conducted due to the decision of the Ministry of Culture of this African country to find out the shell middems' scientific importance.